Three day road eaudiobook - Boyden, Joseph (Recorded Books Inc., 2014)
Author Joseph Boyden makes his debut as a novelist with this Today Book Club pick set during World War I. Moving and tragic, Three Day Road is a profound work that exposes the lasting traumas of war. Cree Indians Xavier Bird and Elijah Whiskeyjack are lifelong best friends from the wilderness of Hudson Bay. Together, they enlist in the Canadian Army in 1915, eager to become heroes. Seasoned moose hunters, they are quickly recognized for their extraordinary accuracy with a rifle and promoted to snipers. But the horrors they must endure in combat begin to eat them alive. In time, only one of them—nightmare plagued, one-legged, and desperately addicted to morphine—will return home to his last remaining relative. This harrowing, yet ultimately redemptive work shows how those who survive war carry the devastation with them for the rest of their lives. "Friendship is riven with resentment and war is stripped of glory in this remarkable, wrenching novel, the work of a gifted storyteller."—Publishers Weekly, starred review